DOI: 10.5642/cguetd/52
|View full text |Cite
|
Sign up to set email alerts
|

Study of Vortex Ring Dynamics in the Nonlinear Schrödinger Equation Utilizing GPU-Accelerated High-Order Compact Numerical Integrators

Abstract: We numerically study the dynamics and interactions of vortex rings in the nonlinear Schrödinger equation (NLSE). Single ring dynamics for both bright and dark vortex rings are explored including their traverse velocity, stability, and perturbations resulting in quadrupole oscillations. Multi-ring dynamics of dark vortex rings are investigated, including scattering and merging of two colliding rings, leapfrogging interactions of co-traveling rings, as well as co-moving steady-state multi-ring ensembles.Simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 100 publications
(160 reference statements)
0
13
0
Order By: Relevance
“…Tsubota et al [21] solved the GPE in 2D to simulate vortex lattice in rotating superfluids, while Kasamatsu et al [22] solved the GPE in 3D and observed vortex tubes with lattice formation. Zuccher et al [23] analyzed the quantum vortex reconnection, while Caplan et al [24] explored vortex ring dynamics. This work adopts a novel superfluid model [6], which covers the entire velocity range and incorporates the previous models as its non-relativistic limit.…”
Section: Related Workmentioning
confidence: 99%
“…Tsubota et al [21] solved the GPE in 2D to simulate vortex lattice in rotating superfluids, while Kasamatsu et al [22] solved the GPE in 3D and observed vortex tubes with lattice formation. Zuccher et al [23] analyzed the quantum vortex reconnection, while Caplan et al [24] explored vortex ring dynamics. This work adopts a novel superfluid model [6], which covers the entire velocity range and incorporates the previous models as its non-relativistic limit.…”
Section: Related Workmentioning
confidence: 99%
“…5, while the unique forms of the Gershgorin disk centers and radii for A ′ are shown in Table 7. The stability bounds are the same as in 191,190,189,174,173,172,156,155,138,36,21,20,6,5,4, −9, −10, −11, −12} .…”
Section: Fourth-order Central Differencementioning
confidence: 99%
“…These driver scripts contain all the code necessary to reproduce the results computed in this paper (as well as those in the author's dissertation [31]). This includes the initial conditions (vortices, vortex rings, etc.…”
Section: The Nlsemagic Code Packagementioning
confidence: 99%